2018
DOI: 10.1159/000488857
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations in Children with a Penicillin Allergy Label: An Assessment of Healthcare Impact

Abstract: Background: Beta-lactam allergy is overdiagnosed. Diagnosis of penicillin allergy has been associated with a greater use of hospital resources and an increased risk of antibiotic-resistant infections, although this issue remains poorly studied in children. We aimed to compare patient characteristics and use of hospital resources in hospitalized children with and without a record of penicillin allergy. Methods: We identified all hospitalizations in children labelled as being allergic to penicillin in a database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Of the 20 studies examining LOS, 11 (55%) found that allergy-labeled patients had significantly longer LOS. 2,19,20,25,29,30,[36][37][38][39][40] Also, 8 studies found equivocal results and 1 found that allergy-labeled patients were hospitalized for shorter duration. 17,21,23,24,[31][32][33]41,42 Of 6 studies, 1 (17%) found that allergylabeled patients were more likely to be admitted to the ICU, but all other studies reported no difference (Table 3).…”
Section: Antibiotic Allergy Labels and Clinical Outcomesmentioning
confidence: 99%
“…Of the 20 studies examining LOS, 11 (55%) found that allergy-labeled patients had significantly longer LOS. 2,19,20,25,29,30,[36][37][38][39][40] Also, 8 studies found equivocal results and 1 found that allergy-labeled patients were hospitalized for shorter duration. 17,21,23,24,[31][32][33]41,42 Of 6 studies, 1 (17%) found that allergylabeled patients were more likely to be admitted to the ICU, but all other studies reported no difference (Table 3).…”
Section: Antibiotic Allergy Labels and Clinical Outcomesmentioning
confidence: 99%
“…16,17 In this study, patients with β-lactam allergy were more likely to receive broader-spectrum antibiotic therapy when compared to nonallergic patients, both in composite and individually. This difference in antibiotic exposure has been shown in most similar studies including a systematic review, [5][6][7][8]10,11,18 and it is generally hypothesized to be the unique driving factor behind many of the negative outcomes reported in patients with antibiotic allergies compared to controls. For example, vancomycin is known to be inferior in the definitive treatment of Staphylococcal bacteremia when compared to antistaphylococcal penicillins or firstgeneration cephalosporins.…”
Section: Discussionmentioning
confidence: 92%
“…8 Previous studies examining hospitalized cohorts of children report that pediatric patients labeled with penicillin allergies frequently receive broader-spectrum antibiotics and experience longer hospital stays with higher overall costs. 10,11 However, these studies have important limitations including relatively small sample sizes, inconsistent approaches to adjust for confounding variables that may differ between allergic and nonallergic controls, and none have been conducted in the United States.…”
mentioning
confidence: 99%
“…In this sense, Abrams et al (2016) proposed a diagnostic protocol for children who are labeled as allergic to beta-lactams and insisted on the importance of correctly labeling the allergy to beta-lactams in the pediatric population, given its low prevalence (Seitz et al, 2011;Abrams et al, 2016;Mill et al, 2016;Roduit, 2019). Sousa-Pinto et al (2018) identified 1,718 hospitalizations corresponding to children with suspected allergy to beta-lactams. These children had more extended days of hospitalization and a higher comorbidity rate.…”
Section: Beta-lactam Studies In Childrenmentioning
confidence: 99%